Direct Comparison Between the Addition of Pembrolizumab or Bevacizumab for Chemotherapy-Based First-Line Treatment of Advanced Non-Squamous Non-Small Cell Lung Cancer Lacking Driver Mutations - Liao, Jiatao; Liu, Chang; Long, Qianqian; Wu, Xianghua; Wang, Huijie; Yu, Hui; Sun, Si; Zhang, Yao; Lin, Ying; Zhao, Xinmin; Wang, Jialei (Frontiers in Oncology, 2021)
1 Background The addition of bevacizumab or pembrolizumab to pemetrexed-platinum chemotherapy has produced significant clinical benefits to patients with untreated, advanced non-squamous non-small cell lung cancer (NSCLC) lacking targetable genetic aberrations. However, the direct comparison between these two first-line treatments needs to be investigated. 2 Methods We retrospectively investigated the medical records of 102 patients with stage ⅢB Ⅳ non-squamous NSCLC, and without sensitizing EGFR/ALK/ROS1 alterations. All patients received pembrolizumab or bevacizumab plus pemetrexed-platinum chemotherapy as the first-line treatment between December 2018 to April 2021 at Fudan University Shanghai Cancer Center. Assessments included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs). We also evaluated the prognostic biomarkers in the overall population and explored potential predictive biomarkers to aid the selection of optimal treatment regimens. 3 Results The median PFS was 10.0 months in the pembrolizumab group and 9.2 months in bevacizumab group (HR = 1.006; P = 0.982), while the median OS was not reached in either group (HR= 1.193; P =0.714). ORR was 36.7% versus 43.4% (P = 0.548) and DCR was 89.8% versus 92.5% (P = 0.735) in the pembrolizumab and bevacizumab groups, respectively. In the overall study population, baseline lymphocyte to monocyte ratio (LMR) >1.95 (HR = 0.312, P < 0.001) was an indicator of longer PFS. The presence of baseline bone metastasis (HR = 4.107, P = 0.009), baseline lactate dehydrogenase (LDH) >300 U/L (HR = 4.300, P = 0.025) and LMR ≤1.95 (HR = 5.291, P = 0.039) were associated with inferior OS. Baseline neutrophil-to-lymphocyte ratio (NLR) ≤3.10 was predictive of significantly favorable OS in the bevacizumab combination treatment (HR = 5.073, P = 0.039). The safety profiles were generally comparable between the two groups. 4 Conclusions In patients with chemotherapy-naive, advanced, non-squamous NSCLC who lack driver mutations, the efficacy and safety of pembrolizumab and bevacizumab when combined with pemetrexed-platinum were comparable. For patients with baseline NLR ≤3.10, the bevacizumab combination therapy elicited significantly better OS benefits.